ENHANCING MARKETING AND MANAGEMENT CAPABILITIES IN THE STRATEGIC DEVELOPMENT OF THE SERVICE SECTOR IN NUKUS CITY FOR SUSTAINABLE ECONOMIC GROWTH AND IMPROVEMENT OF POPULATION WELFARE - Sarsenbaev Bakhitjan Abdulgazievich; Kengesov Diyorbek Umidovich; Nurniyazova Dilnoza Arzubay qizi; Khalmuratova Dilnaz Suleyman qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. This study examines the strategic development of the service sector in Nukus city and the broader Republic of Karakalpakstan from 2017 to 2024, with particular attention to improving marketing and management capabilities as mechanisms for ensuring sustainable economic growth and enhancing the well-being of the population. Based on statistical data analysis, the research reveals a consistent upward trend in service provision, led by sectors such as financial services, transport, and information technologies. The study underscores the imperative of integrating modern marketing strategies and effective management systems to harness the region’s untapped economic potential. Conclusions and recommendations are presented to inform regional development policies.